Marketing of engineering consultancy services : a global perspective - Chatterjee, Pradeep Kumar; Chatterjee, Partho Pratim (ASME Press, 2019)
"Marketing of Engineering Consultancy Services has always been a complex and multi-disciplinary subject, more so in a world of interconnected economies. The cross-border sourcing of services as an integral part of global value chain gained momentum with enhanced economic globalization. We are in the cusp of the creative disruption of Industrial Revolution 4.0 (IR 4.0), where technology is set to change the way we live and work. This technology disruption is spearheaded by Artificial Intelligence (AI), Internet of Things (IoT), and Machine Learning. As the global economy and society undergoes a tectonic shift to post-industrial information society with knowledge capital as its new resource, marketing of services is concurrently experiencing a paradigm shift. This book is a unique blend of the authors' decades of experience in the engineering consultancy service industry, combined with scholarly and academic excellence"--